Community Development Strategy in the Economic Sector for Non-Profit Organization in Simpang Village (Case Study: Pasanggrahan Baranangsiang) - Aliya, Muthi Nur; Rudito, Bambang (International Journal of Economics, Business Management and Accounting (IJEBMA), 2024)
This research focuses on the community development strategy in the economic sector for a non-profit organization in Simpang Village, Indonesia, with a case study of Pasanggrahan Baranangsiang. The study aims to provide an understanding of the social dynamics within Simpang Village, shedding light on the intricacies of its socio-economic condition. It delves into the challenges confronting the residents and identifies key areas that require attention and intervention for the betterment of the community. The paper also emphasizes the need for further research to explore effective collaboration models between the public sector, private sector, and non-profit organizations in the context of community development. The findings of this study are anticipated to contribute valuable insights to the formulation of informed policies and development programs that align with the real needs and aspirations of the Simpang Village community